Extreme wildfire events are linked to global-change-type droughts in the northern Mediterranean - Ruffault, Julien; Curt, Thomas; Martin-StPaul, Nicolas K.; Moron, Vincent; Trigo, Ricardo M. (Natural hazards and earth system sciences, 2018)
Increasing drought conditions under global warming are expected to alter the frequency and distribution of large and high-intensity wildfires. However, our understanding of the impact of increasing drought on extreme wildfires events remains incomplete. Here, we analyzed the weather conditions associated with the extreme wildfires events that occurred in Mediterranean France during the exceptionally dry summers of 2003 and 2016. We identified that these fires were related to two distinct shifts in the fire weather space towards fire weather conditions that had not been explored before and resulting from specific interactions between different types of drought and different fire weather types. In 2016, a long-lasting “press drought” intensified wind-driven fires. In 2003, a “hot drought” combining a heat wave with a press drought intensified heat-induced fires. Our findings highlight that increasing drought conditions projected by climate change scenarios might affect the dryness of fuel compartments and lead to a higher frequency of extremes wildfires events.